Peran Pengadilan Tata Usaha Negara (PTUN) dalam Penyelesaian Sengketa Aparatur Sipil Negara (ASN) - Ramadhani, Nurul Suci; Oktavia, Rindu; Novari, Tahani Haura; Putri, Tefani Yelzah; Hanoselina, Yulia (Inovan Publisher, 2025)
Indonesia as a legal state places the rule of law as the main foundation in the administration of government, including in the management of the Civil State Apparatus (ASN) which consists of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) who often face employment disputes due to official decisions deemed detrimental, such as dismissal, transfer, or disciplinary sanctions. This study aims to analyze the role of the Administrative Court (PTUN) in resolving ASN disputes, examine dispute resolution mechanisms, identify implementation constraints, and formulate strategic efforts to strengthen the effectiveness of PTUN. The research method uses a literature study by examining various scientific sources such as journal articles, books, and relevant laws and regulations. The research findings indicate that PTUN has a vital role in providing legal protection for ASN through the examination of the legality of State Administrative Decisions (KTUN), with resolution mechanisms through administrative efforts to the ASN Consideration Agency (BPASN) and lawsuits to PTUN. However, its effectiveness is hindered by overlapping authorities, lack of legal understanding among ASN, non-compliance with court decisions, and slow judicial processes, thus requiring regulatory harmonization, institutional capacity building, digitalization of the judicial system, legal education, and enforcement of decision implementation to realize justice and legal certainty for ASN as well as a professional and accountable bureaucracy.